Dairy sheep nutrition [ - Bencini, Roberta; Pulina, G. [ (Giuseppe)] (CABI Publishing, 2004)
Sheep milking is widespread throughout the Mediterranean, and is becoming more common in countries such as the UK, USA, Central America, South Africa, Australia and New Zealand. Good nutrition is a critical factor in optimising dairy production from shep.